Efeito do uso de regras e de contingências interdependentes sobre o comportamento de crianças em sala de aula - Izabelly Alexandre dos Passos (2019)
The presence of behavioral problems in the classroom is a recurring complaint from teachers that, besides generating stress for the school staff, can impair the teaching-learning process and the socialization of some students. Researches using group contingencies has been successful in this field. This research aimed to verify the effect of the use of rules and the implementation of interdependent contingencies on the frequency of responses of a 1st grade elementary school. We also sought to evaluate whether the intervention would be effective in modifying behaviors of some specific children, for whom the teacher completed the SNAP-IV questionnaire pre and post intervention. A baseline survey was conducted, in which the frequency of the three target intervention behaviors was raised, followed by two intervention phases, which consisted of the teacher presenting rules on the specific behaviors to be presented for each phase and a daily record of class performance on a board four days a week. A new baseline survey was performed, followed by two other intervention phases and a follow-up 54 days later. In the intervention phases, the achievement of the established criteria resulted in access to a playful activity, chosen by the class, at the end of the week. There was a significant reduction in the rate of responses considered inadequate and an increase in adequate responses during the intervention. Behavior A, “Raising Your Hand to Talk to the Teacher,” positively reinforced, increased attendance from 0 to 0.43 at baseline to an average of 1.33 responses per minute at the end of the last intervention phase. Behavior B, “Going to colleague to talk,” placed under contingency of negative punishment, had response frequency reduced from 0.88 to 1.46 responses per minute at baseline to an average of 0.06 responses per minute. in the last intervention phase. Behavior C, “Calling the teacher in other ways,” for which a contingency of negative punishment was also established, had a frequency reduction from 0.7 to 1.58 responses per minute at baseline to an average of 0.08 responses per minute in the last week of intervention. Group contingency was therefore effective in managing class behavior. Additionally, there was an increase in cooperative behaviors among students. The procedure also seems to have produced changes in the individual behavior of the students indicated by the teacher, who showed a reduction in the SNAP-IV score. The intervention procedure was effective but was not maintained after the end of the research. Individual and institutional aspects were pointed as variables responsible for not maintaining the change. The teacher evaluated the procedure with maximum grade (5 - great) and throughout the year provided positive feedbacks about it. Careful selection of reinforcing items and teacher training contributed to the success of the study.